Integrative research on environmental and landscape change: PhD students’ motivations and challenges - Tress, Bärbel; Tress, Gunther; Fry, Gary (Journal of environmental management, 2009)
The growing demand for integrative (interdisciplinary or transdisciplinary) approaches in the field of environmental and landscape change has increased the number of PhD students working in this area. Yet, the motivations to join integrative projects and the challenges for PhD students have so far not been investigated. The aims of this paper were to identify the understanding of PhD students with regard to integrative research, their motivations to join integrative projects, their expectations in terms of integration and results, and to reveal the challenges they face in integrative projects. We collected data by a questionnaire survey of 104 PhD students attending five PhD Master Classes held from 2003 to 2006. We used manual content analysis to analyse the free-text answers. The results revealed that students lack a differentiated understanding of integrative approaches. The main motivations to join integrative projects were the dissertation subject, the practical relevance of the project, the intellectual stimulation of working with different disciplines, and the belief that integrative research is more innovative. Expectations in terms of integration were high. Core challenges for integration included intellectual and external challenges such as lack of knowledge of other disciplines, knowledge transfer, reaching depth, supervision, lack of exchange with other students and time demands. To improve the situation for PhD students, we suggest improving knowledge on integrative approaches, balancing practical applicability with theoretical advancement, providing formal introductions to other fields of research, and enhancing institutional support for integrative PhD projects.